Subclavian Artery Flow Dynamics Evaluated by Analytical Intraoperative Indocyanine Green Videoangiography During Surgical Treatment of Thoracic Outlet Syndrome: A Case Series. Issue 3 (March 2022) - Kato, Naoki; Terao, Tohru; Ishii, Takuya; Saito, Emiko; Hirokawa, Yusuke; Michishita, Shotaro; Sasaki, Yuichi; Tani, Satoshi; Murayama, Yuichi
Abstract : BACKGROUND: Indocyanine green (ICG) videoangiography is rarely used during the surgical treatment of thoracic outlet syndrome (TOS). OBJECTIVE: To evaluate subclavian artery (SA) flow dynamics using the analytical ICG videoangiography during TOS surgeries. METHODS: We examined patients with neurogenic TOS who received surgical treatment and whose SA blood flow at the interscalene space was evaluated using ICG videoangiography equipped with an analytical function (FLOW800). Anterior scalenectomy with or without middle scalenectomy and first rib resection were conducted for decompression of the brachial plexus. ICG videoangiography was performed before and after decompression of the brachial plexus. After acquisition of grayscale and color-coded maps, a region of interest was placed in the SA to obtain time–intensity diagrams. Maximum intensity (MI), rise time (RT), and blood flow index (BFi) were calculated from the diagram, in arbitrary intensity (AI) units. We compared values before and after decompression. Comparisons of the three parameters before and after decompression were assessed statistically using the paired t -tests and Wilcoxon signed-rank test. RESULTS: We evaluated nine procedures in consecutively presenting patients. The observed mean values of MI, RT, and BFi before decompression were 174.1 ± 61.5 AI, 5.2 ± 1.1 s, and 35.2 ± 13.5 AI/s, respectively, and the observed mean values of MI, RT, and BFi after decompression were 299.3 ± 167.4 AI, 6.6 ± 0.8 s, and 44.6 ± 28.3 AI/s, respectively. These parameters showed higher values after decompression than before decompression, and the increase in MI and RT was statistically significant ( P < .05). CONCLUSION: ICG videoangiography allows semiquantitative evaluation of hemodynamic changes during TOS surgery. A marked decrease in the velocity of SA flow was observed after decompression.